The Impact of Funding Liquidity Risk on Business Discontinuity in the Financial Sector (American Journal of Interdisciplinary Research and Innovation, 2025)
Financing liquidity risk is a serious risk to financial stability especially in the emerging markets, where non-bank financial institutions (NBFIs) have limited regulation along with access to systemic liquidity support. This paper examines the connection between liquidity risk to business discontinuity in NBFI sector between 2011 and 2024 by undertaking a longitudinal quantitative study, and secondary data set of the World bank, and IMF. Major liquidity ratios such as Liquidity Coverage Ratio (LCR), liquid assets percentage, funding ratio, and interest cost were investigated and correlated with macroeconomic factors like the rate of inflation and GDP growth. Regression findings indicate that increase in the LCR, liquid assets and funding ratios greatly decrease the risk of business discontinuity, and increased funding costs and inflation significantly increase risks. Protective effect is also exhibited with credit rating strength. The results are consistent with the goals of Basel III, justifying the significance of strong liquidity buffers, but also show the increased vulnerability of NBFIs to the impact of inflation and borrowing rates. The findings amplify the necessity of extending the regulation of liquidity to NBFIs, enhancing administration, broadening the financing, and shifting toward advanced technologies of forecasting and monitoring. Policy implications include the idea that coordinated non-restrictive monetary and macroprudential policies would facilitate resilience in the sector. This study adds to the international liquidity risk debate and outlines key areas of intervention to reduce the associated operational and reputation-damaging consequences of liquidity crises in the NBFIs.